Acceptability and experience of a functional training programme (ReTrain) in community-dwelling stroke survivors in South West England: a qualitative study. Issue 7 (25th July 2018) - Norris, Meriel; Poltawski, Leon; Calitri, Raff; Shepherd, Anthony I; Dean, Sarah Gerard
Abstract : Rehabilitation Training (ReTrain) is a group-based approach to functional training post stroke. ReTrain has recently been evaluated through a pilot randomised controlled trial. Objective: This article reports on the acceptability of the intervention as described by trial participants. Design: A qualitative approach was undertaken. Of the 45 participants recruited into the trial, 23 were randomised to receive ReTrain. Following a sampling strategy, 10 participants undertook 1:1 semistructured audio-recorded interviews. Transcripts were analysed following a modified Framework Approach. Results: Six themes were developed including exploration of: the physical and psychological impacts of training, the perceived mechanisms of change, the interaction of the group and approach of the trainer. A further theme considered the reported longer term impact of participation. Overall, the results indicated the acceptability of the intervention, but also key areas for potential modification in the definitive trial. These include a need to consider potential impact on both physical and psychological function, careful consideration of dosing and fatigue and the interpersonal factors that facilitate appropriate level of delivery, the trainer to participant ratio, and enhancing features that support continuation of activity postintervention. Conclusion: Overall, this study supports the acceptability of ReTrain and the development of a definitive trial evaluation of this intervention to full. Trial registration number: NCT02429180 .